Culture in Cover and Units’ Covers of Senior High School First Grade Course Book of Curriculum - Indah, Dewi Rosari (JET ADI BUANA, 2017)
Language in any forms, including pictures, conveys massage. Pictures and images carry culture within that reflect attitudes and social life in the world any specific language spoken. Learning English should also be learning its culture to get a better picture of it. One of the sources in learning English is a course book. This article was aimed at finding out what elements that were presented in a senior high school course book of a second grade because of the focus is assumed to be on the lessons in Indonesia. This article report used content analysis as a framework to analyze the culture presented in pictures. It was found that the pictures were well representatives of an English speaking country’s culture. The pictures shared the activities, the seasons, the habit, and the way they dress, behave, and speak that in some ways were different that of Indonesia. The pictures also gave information on different values between Indonesia and English speaking countries